Biobanking in the hospital of a multidisciplinary research medical center as a potential for a wide research range. Part I. Organizational and methodological aspects - A. I. Borisova; O. V. Kopylova; M. S. Pokrovskaya; I. A. Efimova; A. V. Pustelenin; А. I. Ershova; O. M. Drapkina (Кардиоваскулярная терапия и профилактика)
Aim. To develop an algorithm and manage total biobanking of samples of whole blood, serum and plasma of patients in the hospital of the National Medical Research Center for Therapy and Preventive Medicine in order to create a detailed biosample collection through the integration of electronic medical records and a biobank database.Material and methods. The study includes all patients admitted to the hospital of the National Medical Research Center for Therapy and Preventive Medicine in various departments who signed informed consent for biobanking. Clinical information is collected as part of patient examination and stored in electronic medical records in the Medialog medical information system. Biobanking of blood and related products is carried out in accordance with standard operating procedures. From each patient, 12 aliquots of serum and blood plasma are stored, as well as 1 tube of whole blood with ethylenediaminetetraacetic acid potassium salt. Information about biospecimens, patient identification numbers and storage location coordinates are contained in the biobank database.Results. An algorithm for total biobanking of biomaterial and data from inpatients has been developed and put into practice. This collection is associated with large biomedical data stored in a medical information system, laboratory information system and biobank. The combined databases make it possible to search for samples in the collection according to specified criteria.Conclusion. The collection developed can be used for a wide range of studies by forming patient samples according to the necessary criteria. The developed algorithm for total biobanking in a hospital can be used in various medical centers equipped with biobanks.